1988
DOI: 10.1128/mcb.8.12.5108
|View full text |Cite
|
Sign up to set email alerts
|

The intron-containing gene for yeast profilin (PFY) encodes a vital function.

Abstract: The gene coding for profilin (PFY), an actin-binding protein, occurs as a single copy in the haploid genome of Saccharomyces cerevisiae and is required for spore germination and cell viability. Displacement of one gene copy in a diploid cell by a nonfunctional allele is recessively lethal: tetrad analysis yields only two viable spores per ascus. The PFY gene maps on chromosome XV and is linked to the ADE2 marker. The primary transcript of about 1,000 bases contains an intron of 209 bases and is spliced into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 23 publications
2
76
0
Order By: Relevance
“…One of the actin-binding proteins is profilin (3,(5)(6)(7)(8), which has been thought previously to regulate actin filament formation exclusively by sequestering G-actin monomers and thereby to antagonize actin polymerization (3). However, recent results point to a more complex regulation (9).…”
Section: From the Department Biologie I Bereich Genetik Ludwig-maximentioning
confidence: 64%
See 1 more Smart Citation
“…One of the actin-binding proteins is profilin (3,(5)(6)(7)(8), which has been thought previously to regulate actin filament formation exclusively by sequestering G-actin monomers and thereby to antagonize actin polymerization (3). However, recent results point to a more complex regulation (9).…”
Section: From the Department Biologie I Bereich Genetik Ludwig-maximentioning
confidence: 64%
“…Previously we have isolated and characterized the single structural gene for yeast profilin (PFY1) and shown that its deletion leads to a temperature-conditional phenotype. PFY1 is constitutively transcribed at a moderately high level (8,16,17).…”
Section: From the Department Biologie I Bereich Genetik Ludwig-maximentioning
confidence: 99%
“…It has been reported for the transcripts of several yeast genes, e.g. AKY2, PFY, ACT1 and CYC1, that their 3'-untranslated ends are quite long and may extend even more than 150 bases beyond the termination signals [22,[30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…Debris and nuclei were removed (45 000 x g, 30 min) and the RNA purified by centrifugation through a cushion of CsC1 (n = 1.408) [21]. Primer elongation was performed by annealing a denatured, end-labeled 45 bp HinfI/RsaI fragment (position 16 to 60 of the AKY2 coding sequence [16]) to total RNA and elongating the 3 '-end of the DNA primer by murine reverse transcriptase (Pharmacia-PL, Freihurg) as described [22].…”
Section: Preparation Of Rna and Blotting Proceduresmentioning
confidence: 99%
“…As a potential drug target, the fungal profilins, small actin-binding proteins (Witke, 2004), were focused upon in this study, since these proteins are essential for the growth of most eukaryotic cells, including S. cerevisiae (Haarer et al, 1990;Magdolen et al, 1988;Witke, 2004). Furthermore, the existence of structural information (Eads et al, 1998;Haarer et al, 1993) can strongly support the design of structure-based ligands for profilins.…”
Section: Introductionmentioning
confidence: 99%